2019
DOI: 10.3389/fphar.2019.00528
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Intracellular Chaperone Proteins, Sigma Receptors, in Parkinson’s Disease (PD) and Major Depressive Disorder (MDD)

Abstract: Sigma receptors, including Sigma-1 receptors and Sigma-2 receptors, are highly expressed in the CNS. They are intracellular chaperone proteins. Sigma-1 receptors localize mainly at the mitochondria-associated endoplasmic reticulum (ER) membrane (MAM). Upon stimulation, they translocate from MAM to plasma membrane (PM) and nucleus, where they interact with many proteins and ion channels. Sigma-1 receptor could interact with itself to form oligomers, its oligomerization states affect its ability to interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 132 publications
0
24
0
2
Order By: Relevance
“…Sig-1R has been reported to regulate retinal cell pressure [20], to inhibit the neuropathic pain caused by partial sciatic nerve transection in mice [33], to lessen the severity of depressive disorder and to have neurorestorative effects in Parkinson's disease [34]. Sig-1R exerts neuroprotective effects by regulating Ca 2+ homeostasis and preventing glutamate toxicity and neuroinflammation [34]. We found that Sig-1R expression on the ER was significantly upregulated in the early stage of CIRI, and decreased with increasing reperfusion times, consistent with the expression trend of GRP78.…”
Section: Discussionmentioning
confidence: 99%
“…Sig-1R has been reported to regulate retinal cell pressure [20], to inhibit the neuropathic pain caused by partial sciatic nerve transection in mice [33], to lessen the severity of depressive disorder and to have neurorestorative effects in Parkinson's disease [34]. Sig-1R exerts neuroprotective effects by regulating Ca 2+ homeostasis and preventing glutamate toxicity and neuroinflammation [34]. We found that Sig-1R expression on the ER was significantly upregulated in the early stage of CIRI, and decreased with increasing reperfusion times, consistent with the expression trend of GRP78.…”
Section: Discussionmentioning
confidence: 99%
“…The action of Sig-1R in neurons has been revealed to affect neuronal excitability and survival (Yang, Wang, & Sun, 2019). Furthermore, the activation of Sig-1R enhances the neural axonal outgrowth and neurogenesis while knockdown of Sig-1R inhibits hippocampal dendritic spine and synapse formation (Aleksandrova, Phillips, & Wang, 2017;Fukunaga & Moriguchi, 2017;Tsai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sigma1Rs and sigma-2 receptors are different proteins encoded by diverse genes 9,58,59 . The interconnection of these two proteins in physiological processes is poorly understood 6062 . However, the sigma-2 receptor may be a part of the protective pathway that is triggered by the interaction of the Sigma1R chaperone with afobazole.…”
Section: Discussionmentioning
confidence: 99%